The Dynamics of Toothache Pain and Dental Services Utilization: 24-Month Incidence - R. Paul Duncan, PhD; Gregg H. Gilbert, DDS, MBA; Chuck W. Peek, PhD; Marc W. Heft, DMD, PhD (Blackwell Synergy, 2003)
The aims of this study were twofold: (1) to describe patterns of change in reported toothache pain, and (2) to examine the impact of toothache pain on dental care utilization and vice versa